2019
DOI: 10.17159/0379-4350/2019/v72a27
|View full text |Cite
|
Sign up to set email alerts
|

Un-functionalized Gold Nanoparticles as a Simple Colorimetric Probe for Sensitive and Selective Detection of Dopamine

Abstract: A dopamine (DA) colorimetric probe based on the growth and aggregation of un-functionalized gold nanoparticles (AuNPs) is reported. Upon addition of AuNPs to dopamine at various concentrations, the shape, size and colour change of the nanoparticles results in spectral shifts to higher wavelengths and hence colour change is the mode of detection. The colour change can be easily observed by the naked eye from as low as 5.0 nM DA, even under sub-optimal conditions. Under optimal pH conditions the calculated limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
3
0
0
Order By: Relevance
“…1). No colour change or any aggregation was observed during 6 months and that indicated that Au NPs with time lead to form bigger NPs and confirm the results in this work [19]. Furthermore, the UV-Vis spectra of the DNBA-AuNPs solution at the initial time and after 6 months are shown in Fig.…”
Section: Synthesis and Characterization Of Au Nanoparticlessupporting
confidence: 89%
See 2 more Smart Citations
“…1). No colour change or any aggregation was observed during 6 months and that indicated that Au NPs with time lead to form bigger NPs and confirm the results in this work [19]. Furthermore, the UV-Vis spectra of the DNBA-AuNPs solution at the initial time and after 6 months are shown in Fig.…”
Section: Synthesis and Characterization Of Au Nanoparticlessupporting
confidence: 89%
“…Where the intensity steadily increased as a function of time of reaction without any shift in the peak wavelength which confirms what was mentioned in the literature [18]. It is worth mentioning that the stability of AuNPs stable against aggregation was attributed to excess ions of AuCl4and AuCl2which bind to the surface of the AuNPs in the solution during the reduction process of KAuCl4 [19]. UV-Visible spectrum results showed that the SPB of AuNP functionalized by sodium acetate is centred at 536 nm, which is illustrating slightly larger than another ligand that had functionalized AuNPs, which confirm that different ligands were functionalized AuNPs under the same conditions, led to different wavelengths with different stabilities of AuNPs as well.…”
Section: Synthesis and Characterization Of Au Nanoparticlessupporting
confidence: 88%
See 1 more Smart Citation